2018
DOI: 10.22159/ijpps.2018v10i5.25338
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Improvement of Antidiabetic Alpha-Glucosidase Inhibitor Producing Streptomyces Sp

Abstract: Objective: This study aims to control type 2 of diabetes mellitus by a hypoglycemic substance that extensively produced by Streptomyces bacteria. The antidiabetic action of this substance depends on prevention of starch hydrolysis and then the liberation of glucose monomers via an inhibition of α-glucosidase as one of starch hydrolyzing enzymes.Methods: The strains of marine actinomycetes were isolated on starch nitrate agar, and then qualitatively and quantitatively screened to prevent starch hydrolysis. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Therefore, the balance between proliferating biomass and substrate utilization yielded maximum enzyme activity. 58 Abdulkhair et al 59 reported that seven marine Streptomyces isolates exhibited antidiabetic activity due to the production of α-glucosidase inhibitory protein, which was measured spectrophotometrically at 400 nm. The most potent isolate was identified as Streptomyces coelicolor, which showed stable activity for 5 d at 37°C.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the balance between proliferating biomass and substrate utilization yielded maximum enzyme activity. 58 Abdulkhair et al 59 reported that seven marine Streptomyces isolates exhibited antidiabetic activity due to the production of α-glucosidase inhibitory protein, which was measured spectrophotometrically at 400 nm. The most potent isolate was identified as Streptomyces coelicolor, which showed stable activity for 5 d at 37°C.…”
Section: Resultsmentioning
confidence: 99%
“…These results of the FT-IR spectrum suggested that AGIs production S. costaricanus EBL.HB6 could be an alkaloid but not a protein from Streptomyces sp. AD7 [17], or phenolic compounds from Streptomyces sp. OUCMDZ-3434 [9], S. xanthophaeus [13], or dibutyl phthalate from the strain S. melanosporofaciens [22].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that actinobacteria were more prevalent in the discovery of α-glucosidase inhibitors. Abdulkhair (2018) isolated 55 strains of marine Actinomycetes, of which, only 7 strains were found to have α-glucosidase inhibitory activity [17]. S Ganesan, S Raja, P Sampathkumar, K Sivakumar and T Thangaradjou [18] identi ed 41 bacteria strains that exhibited glucosidase inhibitory activity from 181 isolated strains of marine actinobacteria [18].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, they do not affect diabetic bone disorder. Some undesirable impacts on intestinal disturbances such as vomiting, flatulence, diarrhoea, headache, and insomnia, have been described [ 85 , 86 , 89 , 92 ].…”
Section: Treatment Of Type 2 Diabetes Mellitusmentioning
confidence: 99%